Design and implementation of an Openflow SDN controller in NS-3 discrete-event network simulator. (8th May 2019) - Poncea, Ovidiu Mihai; Pistirica, Andrei Sorin; Moldoveanu, Florica; Asavei, Victor
The NS-3 simulator comes with the Openflow protocol and a rudimentary controller for classic layer-2 bridge simulations. This controller lacks basic functionality provided by real SDN controllers, making it inadequate for experimentation in the scientific community. In this paper we propose a new controller with an architecture and functionality similar to that of full-fledge controllers yet simple, extensible and easy to modify - all characteristics specific to simulators.